Surgical management of a child suffering from osteogenesis imperfecta, treated with bisphosphonates - a case report - Małgorzata Lipczyńska-Lewandowska; Piotr Osica; Anna Janas-Naze (Kazimierz Wielki University, 2017)
The article presents a case of surgical extraction of impacted third molars in a 17 y. o. boy with osteogenesis imperfecta.